Training program concern employ energetic learning strategies among Pediatric nursing students: developmental study. - Ahmed Ali, Howaida Moawad (International Journal of Nursing Care)
Background: Strengthening pediatric nursing students to keep pace with digital development so that they can choose an active learning strategy that suits their educational goals, identify educational resources, and have the ability to evaluate themselves. Purpose and design: This study was adopted a quasi-experimental pre and posttest equivalent experiment and control group, design to examine the effects of training program on developmental level of pediatric nursing student’s related to employ energetic learning strategies and self-efficacy. Sample and setting: hundred nursing students who enrolled in Pediatric Nursing course in nursing faculty, Benha university, Egypt. Instruments: Tool 1: The Learning and Study Strategies Inventory (LASSI) to measure learning and study practices and attitudes. Tool II: " Modified Short version self-efficacy (SES) to measure student’s self-efficacy. Tool III: "Modified Short version the flow state scale (FSS) to measure positive optimal experience experiment group only post applies on pediatric nursing course content. Results: There was statistically positive correlation between pediatric nursing students' female gender with urban residence and well-mannered developmental level concerning the Learning and Study Strategies Inventory, employs energetic learning strategies and their self-efficacy soon after training program. The majority of subgroup pediatric nursing students’ trial reported that high score and narrated efficiency learning strategies was animation videos and simulation in practical content and web/computer assisted learning and problem-based learning in theoretical content. Conclusion and recommendation: Research assert that training program was effective and linked with high developmental level of pediatric nursing students about employing active learning strategies and self-efficacy. Distributingthe content of the pediatric nursing curriculum on energetic learning strategies and directing students to learning the course according to the appropriate strategy type this is after their creativity in applying.